2010
DOI: 10.1097/jto.0b013e3181d873be
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration for the Evaluation of Suspected Lymphoma

Abstract: Background: Evidence regarding the utility of endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) in the assessment of isolated mediastinal lymphadenopathy (IMLN) is evolving. Its diagnostic accuracy in the evaluation of suspected lymphoma remains uncertain. Methods: We reviewed a prospectively recorded database of consecutive patients with suspected lymphoma who underwent EBUS-TBNA to evaluate IMLN. Patients in whom EBUS-TBNA was nondiagnostic subsequently underwent surgical biopsy or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(120 citation statements)
references
References 28 publications
5
110
1
1
Order By: Relevance
“…The role of EBUS-TBNA in a lymphoma diagnosis is, therefore, of uncertain value in cases of marginal zone and follicular lymphoma (Farmer and Bailey, 2007). Steinfort et al (2010) reported the value of EBUS-TBNA in mediastinal lymphadenopathies in cases suspicious for lymphoma. They have criticized the use of EBUS-TBNA for some lymphoma subtypes, such as marginal zone lymphomas or hypocellular variants.…”
Section: Discussionmentioning
confidence: 99%
“…The role of EBUS-TBNA in a lymphoma diagnosis is, therefore, of uncertain value in cases of marginal zone and follicular lymphoma (Farmer and Bailey, 2007). Steinfort et al (2010) reported the value of EBUS-TBNA in mediastinal lymphadenopathies in cases suspicious for lymphoma. They have criticized the use of EBUS-TBNA for some lymphoma subtypes, such as marginal zone lymphomas or hypocellular variants.…”
Section: Discussionmentioning
confidence: 99%
“…17 Outside of lung cancer staging, linear EBUS has been shown to be a useful tool for the diagnosis of lymphoma and sarcoidosis. [18][19][20] With the increased demand for this technology, the availability of linear EBUS training in US fellowship programs has yet to be completely addressed.…”
Section: Resultsmentioning
confidence: 99%
“…[11] Since specimens obtained by endobronchial US-guided TBFNAB are not always appropriate for immunohistochemical and flow cytometric examinations, diagnosis of lymphoma subtypes can be difficult. [12] However, recent studies have demonstrated that diagnostic accuracy has significantly improved as a result rapid on-site pathological evaluation. [13] Chemotherapy (CHOP) is the standard treatment for lymphoma.…”
Section: Discussionmentioning
confidence: 99%